Socio-Economic Consequences of Horizontal Gender Inequalities in Education and Health: Incidence from Pakistan (Journal of Asian Development Studies, 2025)
Women make up almost half of the population of Pakistan and contribute significantly to socio-economic development. However, women have been suffering from horizontal and vertical multi-dimensional inequality of opportunities in all spheres of life, especially in education and health. This occurrence of horizontal inequality poses serious socio-economic consequences, leading to poverty, inequality, low productivity, ill health, low life expectancy, and other interrelated problems. In the Gender Inequality Index (GII), the ranking of Pakistan is 135, compared with 127 for Bangladesh and 108 for India. Maternal mortality in Pakistan is highest among all the selected countries and regions. It is 154 per 100,000 births. 32% of the children in Pakistan are out of school. Out-of-school female children constitute 37% of the population, while out-of-school male children are 27%. Education and health facilities for women play a pivotal role in enhancing their productivity and socio-economic development. Mothers with no education have a high infant mortality of 69 per thousand. At the same time, it is reduced to only 32 per thousand for mothers who have matriculation and are above the level of education. The study aims to analyze the socio-economic consequences of horizontal multi-dimensional gender inequalities in education and health faced by women in Pakistan.